529 A comparative case study to understand the enabling factors and barriers to implementing healthwise in selected hospitals in southern africa. (24th April 2018) - Wilcox, Elizabeth; Mabhele, Simphiwe; Romao, Paulo; Spiegel, Jerry; Chimedza, Ida Tsitsi; Zungu, Muzimkhulu; Yassi, Annalee
Abstract : Introduction: HealthWISE is a participatory, quality improvement tool, jointly developed by the International Labour Organisation and the World Health Organisation, to improve the occupational health and safety (OHS) of health workers. Its implementation in practice has been inadequately studied. We therefore conducted a three-country comparative case study in selected hospitals in Mozambique, South Africa and Zimbabwe to better understand the enabling factors and barriers to its implementation. Methods: Pilot implementation of three HealthWISE modules was observed, including planning meetings, Training-of-Trainers (ToT) workshops, action plan development, and check-in visits. Field notes, videotapes of the ToT workshops, monthly reports, and questionnaires supported the analysis. The Promoting Action on Research Implementation in Health Services (PARiHS) framework, which describes successful implementation as a function of evidence, context and facilitation, structured the examination of enabling factors and barriers. Result: Hospitals and participants were selected by local co-investigators and partners. Implementation began with three-day ToT workshops, where 78 participants were trained across the three countries. Action plans detailed activities related to building capacity and raising awareness about OHS. Check-in visits highlighted some misunderstandings related to the roles of the research team and participants in implementation activities. While evidence to support OHS improvements is strong, implementation was constrained by context-related factors such as the steps in obtaining approvals for the research and determining funding flows. The ILO-NIOH-UBC partnership was key in moving activities forward. Discussion: Key steps prior to implementation included strengthening partnerships with stakeholders, and engaging with team members and participants to better understand OHS issues and priorities. Key steps in implementation included training to build local capacity and to empower participants with knowledge and skills to recognise and creatively address workplace issues, and supporting the development of individual hospital action plans that reflected workplace priorities while recognising resource constraints. Administrative hurdles took time to address.